The Evolutionary Map of the Universe pilot survey. (7th September 2021) - Norris, Ray P.; Marvil, Joshua; Collier, J. D.; Kapińska, Anna D.; O'Brien, Andrew N.; Rudnick, L.; Andernach, Heinz; Asorey, Jacobo; Brown, Michael J. I.; Brüggen, Marcus; Crawford, Evan; English, Jayanne; et al.
Abstract: We present the data and initial results from the first pilot survey of the Evolutionary Map of the Universe (EMU), observed at 944 MHz with the Australian Square Kilometre Array Pathfinder (ASKAP) telescope. The survey covers $270 \, deg^2$ of an area covered by the Dark Energy Survey, reaching a depth of 25–30 $μ\mathrm{Jy\ beam}^{-1}$ rms at a spatial resolution of $\sim$ 11–18 arcsec, resulting in a catalogue of $\sim$ 220 000 sources, of which $\sim$ 180 000 are single-component sources. Here we present the catalogue of single-component sources, together with (where available) optical and infrared cross-identifications, classifications, and redshifts. This survey explores a new region of parameter space compared to previous surveys. Specifically, the EMU Pilot Survey has a high density of sources, and also a high sensitivity to low surface brightness emission. These properties result in the detection of types of sources that were rarely seen in or absent from previous surveys. We present some of these new results here.